Kallikrein‐related peptidase 5 contributes to the remodeling and repair of bronchial epithelium. Issue 10 (28th September 2021) - Lenga Ma Bonda, Woodys; Lavergne, Marion; Vasseur, Virginie; Brisson, Lucie; Roger, Sébastien; Legras, Antoine; Guillon, Antoine; Guyétant, Serge; Hiemstra, Pieter S.; Si‐Tahar, Mustapha; Iochmann, Sophie; Reverdiau, Pascale
Abstract: Inflammation, oxidative stress, and protease/protease inhibitor imbalance with excessive production of proteases are factors associated with pathogenesis of the chronic obstructive pulmonary disease (COPD). In this study, we report that kallikrein‐related peptidase 5 (KLK5) is a crucial protease involved in extracellular matrix (ECM) remodeling and bronchial epithelial repair after injury. First, we showed that KLK5 degrades the basal layer formed by culture of primary bronchial epithelial cells from COPD or non‐COPD patients. Also, exogenous KLK5 acted differently on BEAS‐2B cells already engaged in epithelial‐to‐mesenchymal transition (EMT) or on 16HBE 14o‐ cells harboring epithelial characteristics. Indeed, by inducing EMT, KLK5 reduced BEAS‐2B cell adherence to the ECM. This effect, neutralized by tissue factor pathway inhibitor 2, a kunitz‐type serine protease inhibitor, was due to a direct proteolytic activity of KLK5 on E‐cadherin, β‐catenin, fibronectin, and α5β1 integrin. Thus, KLK5 may strengthen EMT mechanisms and promote the migration of cells by activating the mitogen‐activated protein kinase signaling pathway required for this function. In contrast, knockdown of endogenous KLK5 in 16HBE14o‐ cells, accelerated wound healing repair after injury, and exogenous KLK5 addition delayed the closure repair. These data suggest that among proteases, KLK5 could play a critical role in airway remodeling events associated with COPD during exposure of the pulmonary epithelium to inhaled irritants or smoking and the inflammation process.